Efektivitas Model Project Based Learning Berbantuan Educaplay dalam Meningkatkan Motivasi Belajar Fisika - Trisdayanti, Emi; Harahap, Rofiqoh Hasan; Siregar, Shinta Marito; Nasution, Lia Afriyanti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study investigates the effect of the Project Based Learning (PjBL) model integrated with Educaplay media on students’ motivation in learning Newton’s Laws. A quasi-experimental quantitative design was employed, involving an experimental class and a control class. Data were collected through achievement tests and motivation questionnaires, and analyzed using descriptive and inferential statistics. The findings show a substantial increase in students’ motivation in the experimental class, reaching 81.5%, compared to 68.7% in the control class. The hypothesis test yielded a significance value of 0.001 < 0.05, indicating a significant positive effect of the PjBL–Educaplay integration. Unlike previous studies focusing on general digital media effectiveness, this study highlights the specific advantage of combining PjBL with interactive platforms to enhance motivation in physics learning